Integrated emergency medical services during COVID-19 crisis - Banjade, Prakash; Nasir, Ahmeed; Bhandari, Jeetendra; Rajak, Ashik (Journal of General Practice and Emergency Medicine of Nepal, 2024)
The COVID-19 pandemic prompted rapid adjustments in pre-hospital emergency medical services. Providers faced significant exposure during aerosolization-risk procedures like airway management and resuscitation. Equipping and training personnel with proper protective gear is crucial. Complex inter-hospital transfers mainly involve intubated COVID-19 patients. To manage resource shortages, pre-hospital triage recommendations should align with hospital processes. Patient orientation—home, hospitalization, or ICU admission—is vital. Hospitals shifted from systematic case recognition to epidemic mitigation, ensuring adequate capacity.